Behavioral Inhibition and Activation Systems, and Emotional Regulation in Individuals With Chronic Musculoskeletal Pain - Serrano-Ibáñez, Elena R.; Ramírez-Maestre, Carmen; López-Martínez, Alicia E.; Esteve, Rosa; Ruiz-Párraga, Gema T.; Jensen, Mark P. (Frontiers in Psychiatry, 2018)
Gray’s Reinforcement Sensitivity Theory postulates two distinct neurophysiological systems that underlie the thoughts, emotions, and behavior: Behavioral Inhibition system (BIS) and Behavioral Approach System (BAS). Preliminary research suggests that both may play important role in the adjustment of individuals with chronic pain. However, the extent to which emotional regulation mediates the associations between BIS and BAS activation and emotional responses in individuals with chronic pain have not yet been evaluated. The aim of this study was to test a hypothetical model regarding the associations between BIS and BAS, emotional regulation and adjustment in individuals with chronic musculoskeletal pain. Five hundred and sixteen participants were interviewed and Structural Equation Modelling was used to test the association between variables (BIS, and BAS, expressive suppression, and cognitive reappraisal, negative and positive affect). The empirical model showed a good fit to the data (χ2/df = 1.95; RMSEA = 0.04; GFI = 0.99; AGFI = 0.98; CFI = 0.99). We found that BIS and BAS were related to both negative and positive affect. BIS was also related to emotional regulation (expressive suppression and cognitive reappraisal). Expressive suppression was associated positively to negative affect, and cognitive reappraisal was associated with both negative and positive affect. The current findings indicate that BIS, in particular, and BAS, to a lesser extent, play roles in the emotional functioning in patients with chronic pain. The findings provide new and important information regarding the potential role that BIS and BAS have as predictors of psychological function in individuals with chronic pain. The results suggest the possibility that treatments directed to emotional regulation could potentially reduce the negative impact that chronic pain has via BIS.